ACUTE ANKLE SPRAIN INJURY ALTERS KINEMATIC AND CENTRE OF PRESSURE MEASURES OF POSTURAL CONTROL DURING SINGLE LIMB STANCE. Issue 7 (11th March 2014) - Doherty, C; Delahunt, E; Bleakley, C; Hertel, J; Ryan, J; Caulfield, B
Abstract : Background: Upright single-limb stance (SLS) is maintained via integration of visual, vestibular and somatosensory afferents. The presence of redundancies between these afferents allows the sensorimotor system to simplify a specific task within a number of strategies. Musculoskeletal injury challenges the somatosensory system to reweight distorted sensory afferents. No current investigation has supplemented kinetic analysis of eyes-open and eyes-closed SLS tasks with a kinematic profile of lower limb postural orientation in an acute lateral ankle sprain (LAS) group to assess the adaptive capacity of the sensorimotor system to injury. Objective: To compare centre of pressure (COP) and lower limb postural orientation characteristics of participants with acute LAS to non-injured participants during a SLS task. Design: Cross-sectional. Setting: University biomechanics laboratory. Participants: 66 participants with acute LAS completed a task of eyes-open SLS on their injured and non-injured limbs (task 1). 23 of these participants successfully completed the SLS task with their eyes closed (task 2). A non-injured control group of nineteen participants completed task 1, with 16 completing task 2. Main outcome measures: 3D kinematics of the hip, knee and ankle joints as well as associated fractal dimension (FD) of the COP path. Results: Between trial analyses of groups revealed significant differences in lower limb kinematics and FD of the COP path for task 2. Post-hoc testing revealed that non-injured control group bilaterally assumed a position of greater hip flexion compared to LAS participants (injured limb=7.41±6.1 ◦ vs 1.44±4.8 ◦ ; non-injured limb=9.59±8.5 ◦ vs 2.16±5.6 ◦ ), with a corollary of greater FD of the COP path (injured limb=1.39±0.16 vs 1.25±0.14; non-injured limb=1.37±0.21 vs 1.23±0.14). Conclusion: Acute LAS causes bilateral impairment in postural control strategies.